Explaining the stability of cooperation in agricultural industry chains based on the institutional theory: Multiple mediating effects of perceived value and trust - Zhao, Rong-Rong; Wang, Qiao; Tian, Yuan; Chen, Qiu-Hua (Frontiers in Psychology, 2023)
Due to the superposition of multiple complex socioeconomic environments and the complexity and uncertainty of the agricultural industry chain itself, the agricultural industry chain has become unstable, jeopardizing its long-term sustainability. The purpose of this study is to construct and validate a stability mechanism model of cooperative relationships within agricultural industry chains based on the institutional theory. The questionnaire survey method was used for empirical analysis. The results show that imitative pressure, mandatory pressure, and normative pressure have significant positive effects on the stability of cooperative relationships in agricultural industrial chains. Besides, perceived benefits, perceived risks, and trust play composite multiple mediating roles between imitative pressure and cooperation stability, and between normative pressure and cooperation stability in agricultural industrial chains. Perceived benefits and trust play partial mediating roles in the stability of cooperative relationships between mandatory pressure and agricultural industrial chains. This study is conducive to further understanding the cooperative psychology of agricultural industry chain operators. And this research can provide a reference for managers to take targeted measures to deal with the instability in the development of agricultural industry chains.